Modeling & Analysis of a Novel Adaptive Hysteresis Band Controller for Boost and Buck Converter - Tanmoy Roy Choudhury; Byamakesh Nayak (Institute of Advanced Engineering and Science, 2017)
In this paper, a new topology of Adaptive Hysteresis Band controller for Boost & Buck converter has been proposed, modeled and analyzed. The difficulties caused in Hysteresis Band (HB) controlled dc-dc converter have been eliminated using Adaptive Hysteresis Band (AHB) controller. This novel control topology can be able to maintain the switching frequency constant unlike HB controller. Thus the filter design for the converters will become easier with this controller. Again this control methodology is a robust one as it depends upon the system parameters where there was no possibility with HB controller. The Mathematical modeling of the controller is shown in this paper, further this has been simulated using Matlab /SIMULINK to generate pulse. The steady state analysis to find the parameters and the stability condition of the converter using the dynamic behavior is also portrayed in this paper. The simulation for a Boost and a Buck converter is also shown separately using AHB controller.